Addition of compatibilized nanoclay and UHMWPE fibers to epoxy based GFRPs for improved mechanical properties. (June 2021) - Shelly, Daksh; Nanda, Tarun; Mehta, Rajeev
Abstract: Epoxy based glass fiber reinforced composite laminates containing silanized nanoclay and compatibilized ultra-high molecular weight polyethylene (UHMWPE) fibers were processed using vacuum assisted resin infusion moulding for improved mechanical properties. UHMWPE fibers are low-cost, light-weight with excellent impact strength (highest among thermoplastic fibers), tensile strength and modulus. X-ray diffraction/transmission electron microscopy validated nano-level dispersion of nanoclay. Silanization of nanoclay was validated by Fourier-transform infrared spectroscopy. UHMWPE fibers were compatibilized using three different surface treatments and their compatibilization was confirmed by energy dispersive spectroscopy. Nanocomposite reinforced with 2 phr silanized nanoclay and 0.25 phr compatibilized UHMWPE fibers (treated using the best method) showed significant improvement of 30% in impact strength over the reference sample (all other mechanical properties also showed significant improvements). SEM analysis confirmed that silanization of nanoclay and compatibilization of UHMWPE fibers through the optimum treatment resulted in enhanced interfacial bonding among different constituents of the GFRP nanocomposite system.